Strategi Pengembangan Kemampuan Penindakan Huru Hara Anggota Satuan Brigade Mobil (Satbrimob) dalam Rangka Peningkatan Profesional Polri (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2026)
This research is motivated by the importance of improving the professionalism of Satbrimob in riot control so that its actions remain firm, legal, proportional, accountable, and respectful of human rights. The objectives of this study are to analyze the regulations and existing conditions of the riot control capabilities of Satbrimob personnel, identify factors that hinder professionalism, and formulate an ideal and implementable capability development strategy. The type of research used is empirical juridical research with a socio-legal research approach, conducted through library research, interviews, limited observation, and normative-qualitative analysis. The results of the study indicate that the legal basis and standard operating procedures for riot control are relatively strong; however, their implementation has not been optimal due to the gap between regulations and field practices. The main obstacles include legal, institutional, human resource, infrastructure, and organizational culture aspects. The required strategies include realistic scenario-based training, strengthening field leadership, modernizing non-lethal equipment, improving tactical communication, and conducting continuous evaluation. This study recommends that Satbrimob strengthen human rights-based training, emotional control, cross-functional coordination, and a humanistic organizational culture so that riot control can be carried out professionally and gain public trust.